2020
DOI: 10.1159/000514341
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence during the COVID-19 Pandemic in Portugal

Abstract: The measures implemented to combat the COVID-19 pandemic led populations to confinement at home, with increased risk of domestic violence due to extended shared time between victims and offenders. Evidence on domestic violence in times of pandemic is lacking. This study examines the occurrence of domestic violence, associated factors and help seeking during the COVID-19 pandemic. An online survey was conducted in Portugal between April and October 2020 by NOVA National School of Public Health. The survey was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 24 publications
4
26
2
4
Order By: Relevance
“…In Australia, a 5% increase in domestic violence has been recorded [94][95][96]. In a study in Portugal that consisted of 1062 participants, 13.7% reported experiencing some form of domestic violence [97]. In France, reports increased by 30%, while a 25% increase was seen in Argentina and a 30% increase was noted in Cyprus.…”
Section: Sexual and Domestic Violencementioning
confidence: 99%
“…In Australia, a 5% increase in domestic violence has been recorded [94][95][96]. In a study in Portugal that consisted of 1062 participants, 13.7% reported experiencing some form of domestic violence [97]. In France, reports increased by 30%, while a 25% increase was seen in Argentina and a 30% increase was noted in Cyprus.…”
Section: Sexual and Domestic Violencementioning
confidence: 99%
“…The survey results in Portugal showed that during the COVID-19 pandemic, as many as 62.3% of domestic violence victims were reluctant to access assistance [30]. Victims of violence are reluctant to report because they think it is unnecessary, even if they are afraid to be blamed (victim-blaming) [30], [31].…”
Section: Based On Table 2 the Domestic Violence Cases During The Covid-19 Pandemic Decreased To 5584% Frommentioning
confidence: 99%
“…The emotional fallout of social distancing is intense and diverse. Risk factors associated with potential suicidal behaviors (e.g., trauma, abuse, social isolation, job and financial losses and mental health disorders, among others) in association with barriers to accessing basic services, including health, have been exacerbated during this pandemic [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the face of the lack of evidence on the mental health impact of this “new” disease, the NOVA National School of Public Health, in collaboration with Ghent University, launched a research project about violence and the impact of COVID-19 [ 16 ], which was developed with other Portuguese university partners. The project was focused on intimate partner violence and aimed to better understand the impact of the lockdown measures on the Portuguese population, shedding light on the self-reported occurrence of domestic violence and associated sociodemographic factors as well as on mental health problems related to pandemic times.…”
Section: Introductionmentioning
confidence: 99%